2010
DOI: 10.1039/b922797k
|View full text |Cite
|
Sign up to set email alerts
|

Understanding microwave heating effects in single mode type cavities—theory and experiment

Abstract: This paper explains the phenomena which occur in commercially available laboratory microwave equipment, and highlights several situations where experimental observations are often misinterpreted as a 'microwave effect'. Electromagnetic simulations and heating experiments were used to show the quantitative effects of solvent type, solvent volume, vessel material, vessel internals and stirring rate on the distribution of the electric field, the power density and the rate of heating. The simulations and experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
145
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(156 citation statements)
references
References 40 publications
6
145
0
3
Order By: Relevance
“…Whilst the mechanistic principals were beginning to be understood (Kingman et al, 2000a), it was found that reductions in energy inputs (from >>10kWh/t to <5kWh/t) and residence times (to yield higher throughputs) were required to realise an economically viable process (Kingman and Rowson, 1998). Focussed work using single mode cavities, post-2000 resulted in reductions in the energy required, greater understanding of the breakage mechanism and also characterisation of the electromagnetic properties of such cavities (Kingman et al, 2004c;Kingman et al, 2000b;Robinson et al, 2010a). This yielded important information regarding the spatial distribution and intensity of electromagnetic energy within them.…”
Section: Microwave Processing Of Ores -Technology Development Timelinementioning
confidence: 99%
“…Whilst the mechanistic principals were beginning to be understood (Kingman et al, 2000a), it was found that reductions in energy inputs (from >>10kWh/t to <5kWh/t) and residence times (to yield higher throughputs) were required to realise an economically viable process (Kingman and Rowson, 1998). Focussed work using single mode cavities, post-2000 resulted in reductions in the energy required, greater understanding of the breakage mechanism and also characterisation of the electromagnetic properties of such cavities (Kingman et al, 2004c;Kingman et al, 2000b;Robinson et al, 2010a). This yielded important information regarding the spatial distribution and intensity of electromagnetic energy within them.…”
Section: Microwave Processing Of Ores -Technology Development Timelinementioning
confidence: 99%
“…There are a number of techniques whereby spot-measurements of temperature can be made in a microwave environment, however these are point-measurements within a media with a significant temperature distribution. It has also been shown that the addition of a thermocouple causes a significant distortion to the electric field [19], so the readings obtained are partly an artefact of the presence of the thermocouple rather than the behaviour of the sample under study. There are no reliable ways to measure the temperature distribution during microwave heating, so any data interpretation must not rely directly on these measurements.…”
Section: Microwave Pyrolysis -A Volumetric Heating Approachmentioning
confidence: 99%
“…It was noticed that around the edges of internal protruding objects (such as stirrers and temperature probes) the electric field and power density were significantly concentrated ( Figure 8). Furthermore, the volume of solvent present in a reaction vessel has an effect on the distribution of the electric field [190].…”
Section: Microwave Apparatus and The Importance Of Cavity Designmentioning
confidence: 99%
“…The majority of the aforementioned studies in this review report the use of domestic MW which feature built-in agitation devices, temperature monitoring/control of the reaction mixture with either infrared sensors or fibre optic probes and software which enables the user to monitor the temperature/pressure of the reaction [190]. However, one of the main limitations with such devices (and also a limitation of domestic MW ovens) is the relatively low intensity electric field and the absence of reflected power measurements.…”
Section: Microwave Apparatus and The Importance Of Cavity Designmentioning
confidence: 99%
See 1 more Smart Citation